Electrochemical Characterization of Platinum Nanotubules Made via Template Wetting Nanofabrication - Eric Broaddus; Joel Brubaker; Scott A. Gold (International Journal of Electrochemistry)
Standard oxidation-reduction reactions such as those of ferrocyanide and ferrocene have long been employed in evaluating and comparing new electrode structures with more traditional configurations. A variety of nanostructured carbon electrodes developed in recent years have been reported to exhibit faster electron transfer kinetics than more traditional carbon structures when studied with these redox reactions. This type of comparison has not been widely explored for nanostructured platinum electrodes that have become increasingly common. In this work, a platinum nanotubule array electrode was fabricated via a simple template-based process and evaluated using the standard ferrocyanide redox reaction. The nanotubule array electrodes were observed to more closely approach ideal reversible behavior than a typical Pt black/Nafion fuel cell electrode or a standard polished Pt disc electrode. The apparent heterogeneous electron transfer coefficient was determined using the Nicholson method and found to be one to two orders of magnitude greater for the nanotubule array electrodes, depending on the diameter of the nanotubules, in comparison with these same two more traditional electrode structures.